Learners' orientations in second language learning: Determining their performance in ESL / Khalid Mat Pardi …[et al.] - Mat Pardi, Khalid; Abd Kadir, Nor Aziah; Joseph, Caroline; Aminullah, Rosita; Bakar, Sulaila (2013)
Students' achievements in English as a second language (ESL) have always been an issue in Malaysia. The government has put in efforts to improve students' proficiency level of English; yet students have not been performing well. This paper is an attempt to determine the purpose of the learners in learning English and to investigate the relationship between the orientations towards their performance in ESL. A purposeful sampling in survey design was used in collecting the data. 30 Maktab Rendah Sains MARA Serting students were chosen as the respondents. This data then was analysed to get the inferential statistics. It was later found that learners who learned English under the either integrative or instrumental orientation have no relationships towards their ESL performance.